What is sustainable fashion?. Issue 4 (3rd October 2016) - Henninger, Claudia E.; Alevizou, Panayiota J.; Oates, Caroline J.
Abstract : Purpose: The purpose of this paper is to examine what the term sustainable fashion means from the perspective of micro-organisations, experts, and consumers. Design/methodology/approach: This research is qualitative in nature, utilising a multi-methods case study approach (semi-structured interviews, semiotics, questionnaires). Grounded analysis was applied to analyse the data. Findings: Findings indicate that interpretation of sustainable fashion is context and person dependent. A matrix of key criteria provides the opportunity to find common elements. Research limitations/implications: Due to the nature of this research the sample size is limited and may not be generalised. Data were collected in the UK and are limited to a geographical region. Practical implications: An important implication is that defining sustainable fashion is vital in order to avoid challenges, such as greenwashing, which were faced in other industries that have a longer history in sustainable practices. Micro-organisations should take advantage of identifying key sustainable fashion criteria, which will enable them to promote their fashion collections more effectively. Social implications: The criteria identified provide assurance for consumers that sustainable fashion is produced with social aspects in mind (fair wages, good working conditions). Originality/value: The paper proposes a matrix that allows micro-organisations to clearly identify their collections as sustainable.